Mortality Rates in People With Convulsive Epilepsy in Rural Northeast China - Li, Jing; Zhang, Xinyue; Li, Nan; Zhao, Danyang; Li, Guangjian; Lin, Weihong (Frontiers in Neurology, 2020)
Purpose: To examine the mortality rate and causes of death of phenobarbital (PB) monotherapy and sodium valproate (VPA) monotherapy in patients with convulsive epilepsy in rural northeast China and compare the differences in the results between the two antiepileptic drugs. Methods: Patients with convulsive epilepsy were recruited by trained public health workers in a project for epilepsy prevention and treatment. Patients were enrolled between January 2010 and December 2018 and were treated with PB or VPA. Mortality rate (MR), the proportional mortality ratio (PMR) for each cause, standardized mortality ratio, and years of potential life lost (YPLL) for sex, age, and cause were estimated based on the 2018 Chinese rural population. Results: A total of 3,916 patients with convulsive epilepsy enrolled in the study, of whom 3,418 received PB and 498 received VPA. There were 325 reported deaths (300 from the PB group) during the follow-up period. The MRs were 9.96 and 5.73% in the PB and VPA groups, respectively. The overall SMRs were 12.92 (95% confidence intervals [CI]: 11.50–13.93) and 7.39 (95% CI: 4.78–10.91), for the PB and VPA groups, respectively. Cerebrovascular disease and heart disease were the major causes of death in both treatment groups. The average YPLL for the PB group (21.9 years) was higher than that for the VPA group (13.4 years). Conclusion: This is the first epidemiological study to examine the MR of patients with epilepsy in rural northeast China. Our study is somewhat different from previous studies reported in China, and we provide new relevant data from northeast China.